Ethical leadership, perceived organizational support and citizenship behaviors: The moderating role of ethnic dissimilarity. Issue 8 (27th November 2019) - Tan, Luen Peng; Yap, Ching Seng; Choong, Yuen Onn; Choe, Kum Lung; Rungruang, Parisa; Li, Zhen
Abstract : Purpose: Utilizing organizational support theory, the purpose of this paper is to examine the mediation effect of perceived organizational support (POS) on the relationship between ethical leadership and citizenship behavior, and investigate the moderating effect of ethnic dissimilarity in the research model. Design/methodology/approach: Using a self-administered questionnaire, data were collected from 294 academics of private universities in China, Malaysia and Thailand. The collected data were analyzed using partial least squares path modeling technique on R platform. Findings: The study found that ethical leadership is significantly and positively related to POS, which, in turn, related to both distinct dimensions of organizational citizenship behaviors – individual and organization. However, further analysis reveals that ethnic dissimilarity does moderate the hypothesized relationships in the research model, in which POS is found to have a mediation effect in the heterogeneous sample but not in the homogeneous sample in terms of ethnic dissimilarity. Originality/value: To the best knowledge of the researchers, this study is among the first few research works examining the interrelationships of ethical leadership, POS, and citizenship behavior in terms of individual and organizational. Moreover, this is one of the earliest studies to examine the concepts in two different samples in terms of ethnic dissimilarity.